Technical Review on Electromagnetic Inverse Scattering - Meenaketan, Babu Linkoon P.; Pal, Srikanta; Chattoraj, N. (Journal of Graphic Era University, 2023)
<span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*301.37px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.963207);" role="presentation">Electromagnetic inverse scattering is a method to identify the geometry, location and materi<span dir="ltr" style="left: calc(var(–scale-factor)*459.46px); top: calc(var(–scale-factor)*301.37px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.970609);" role="presentation">al properties of <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*314.57px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.916753);" role="presentation">unknown target<span dir="ltr" style="left: calc(var(–scale-factor)*134.54px); top: calc(var(–scale-factor)*314.57px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.914295);" role="presentation">/targets using the collected scattered field data which may be due to known or <span dir="ltr" style="left: calc(var(–scale-factor)*451.06px); top: calc(var(–scale-factor)*314.57px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.899985);" role="presentation">unknown sources. <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*327.77px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.935938);" role="presentation">This area of research also extended to work with the dynamic object where the objective is to retrieve velocity <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*340.97px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.945368);" role="presentation">profile along with its general properties. <span dir="ltr" style="left: calc(var(–scale-factor)*239.09px); top: calc(var(–scale-factor)*340.97px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.923438);" role="presentation">Here we represent all the major development done in electromagnetic <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*354.29px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.898764);" role="presentation">inverse scatteri<span dir="ltr" style="left: calc(var(–scale-factor)*132.26px); top: calc(var(–scale-factor)*354.29px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.912401);" role="presentation">ng both in static and dynamic platform since last four decades both in time and frequency domain <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*367.49px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.964918);" role="presentation">with its working principle, ad<span dir="ltr" style="left: calc(var(–scale-factor)*191.81px); top: calc(var(–scale-factor)*367.49px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.920628);" role="presentation">vantages, and its limitations. <span dir="ltr" style="left: calc(var(–scale-factor)*310.13px); top: calc(var(–scale-factor)*367.49px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.916107);" role="presentation">We also provided a comprehensive discussion of the <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*380.69px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.905369);" role="presentation">basic theory of inverse scattering analysis bot<span dir="ltr" style="left: calc(var(–scale-factor)*254.21px); top: calc(var(–scale-factor)*380.69px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.911044);" role="presentation">h in the static and dynamic domain.